2002
DOI: 10.1016/s0014-5793(02)02877-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial homocitrate synthase involved in lysine biosynthesis

Abstract: In Thermus thermophilus homocitrate synthase (HCS) catalyzes the initial reaction of lysine biosynthesis through K K-aminoadipic acid, synthesis of homocitrate from 2-oxoglutarate and acetyl-CoA. HCS is strongly inhibited by lysine, indicating that the biosynthesis is regulated by the endproduct at the initial reaction in the pathway. HCS also catalyzes the reaction using oxaloacetate in place of 2-oxoglutarate as a substrate, similar to citrate synthase in the tricarboxylic acid cycle. Several other propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 26 publications
0
44
0
Order By: Relevance
“…Steady state kinetic analysis of the Zn(II)-bound form of WT SpHCS yielded k cat and K m values for AcCoA and 2-OG (Fig. 4, A and B, and (11,32). We then measured the kinetic parameters for conservative and alanine substitutions of the active site residues that interact with 2-OG (Fig.…”
Section: Volume 284 • Number 51 • December 18 2009mentioning
confidence: 99%
“…Steady state kinetic analysis of the Zn(II)-bound form of WT SpHCS yielded k cat and K m values for AcCoA and 2-OG (Fig. 4, A and B, and (11,32). We then measured the kinetic parameters for conservative and alanine substitutions of the active site residues that interact with 2-OG (Fig.…”
Section: Volume 284 • Number 51 • December 18 2009mentioning
confidence: 99%
“…In the case of the enzyme from Penicillium chrysogenum, the inhibition by lysine was shown to be competitive with respect to ␣-ketoglutarate and pH-dependent with only 20% inhibition by 1 mM lysine at pH 6.6 -7.0 (10). It has also been reported that HCS from Thermus thermophilus is highly sensitive to lysine (11). Regulation of HCS activity by CoA and divalent metal ions has also been reported (12).…”
mentioning
confidence: 95%
“…We have shown that in an extremely thermophilic bacterium, Thermus thermophilus HB27, lysine is synthesized through ␣-aminoadipate, although lysine is synthesized through diaminopimelate in most bacteria (13,18,20,22,23,31). We have previously characterized HICDH from T. thermophilus HB27 (TtHICDH) in detail and have shown that the enzyme has four unique features (19).…”
mentioning
confidence: 99%